The Imposition of Criminal Sanctions for Embezzlement Viewed From Comparative Analysis - Vista Lestari, Novia (Universitas Negeri Gorontalo, 2024)
The purpose of this study was to find out the comparative imposition of sanctions on the crime of embezzlement at the Limboto District Court and the implications of the crime of embezzlement in office. The type of research used is normative legal research, with statutory and case approaches. Comparative of the imposition of sanctions and the way the judge applies the decision, namely the judge gives a very light decision on Decision Number 151/Pid.B/2019/PN.Lbo with the relief that the defendant is 8 months pregnant and there is government regulation No. 32 of 1999 in Article 20 Pregnant women convicts while in the penitentiary the detention of pregnant women prisoners is not made and the judge in implementing the decisions in both cases takes decency in the trial to lighten his decision.